2013
DOI: 10.1155/2013/748294
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Concrete Columns Repaired with Polymer Mortar and Epoxy Fiber Panel

Abstract: Underwater structures are not easy to check for the degree of damage or to repair and strengthen damaged regions. Even during repair and strengthening, quality control is very difficult, because the work is done under water. Moreover, underwater structures severely deteriorate, owing to special environmental conditions. If this deterioration continues, the structures face serious structural problems, because of the corrosion of steel rods and the loss of concrete sections. Repairing or strengthening underwater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Materials like polymers may also be introduced into the composition. According to Hong and Park [14], incorporation of polymers does not only help in the increment of strength and reduction of bleeding and shrinkage, it also gave a drawback to the composition where it contributes to the cohesiveness of the fresh grout composition.…”
Section: Objectivesmentioning
confidence: 99%
“…Materials like polymers may also be introduced into the composition. According to Hong and Park [14], incorporation of polymers does not only help in the increment of strength and reduction of bleeding and shrinkage, it also gave a drawback to the composition where it contributes to the cohesiveness of the fresh grout composition.…”
Section: Objectivesmentioning
confidence: 99%
“…Repairs of the underwater concrete structures are complicated construction works due to the constant dynamic action of water on these structures. It has been reported that a material used to repair concrete cracks in dry conditions is invalid in the underwater condition since it often fails to bond to the damaged concrete and adverse effects can occur with the reaction between the hardener and the water [25,26]. For example, the curing agent in epoxy mortar reacts with water and carbon dioxide, which leads to a sharp decrease in bond strength [27].…”
Section: Introductionmentioning
confidence: 99%